Biomechanical analysis of locking reconstruction plate using mono-or bicortical screws - Santos, Rogerio Rodrigues [UNESP]; Rahal, Sheila Canevese [UNESP]; Neto, Camilo Mesquita; Ribeiro, Celso Roberto; Sousa, Edson Antonio Capello [UNESP]; Foschini, Cesar Renato [UNESP]; Agostinho, Felipe Stefan [UNESP]; Dos Reis Mesquita, Luciane [UNESP] (FapUNIFESP (SciELO), 2016)
This experimental in vitro study evaluated the influence of screw length on the mechanical properties of a locking reconstruction plate designed with locking rings inserted into plate holes. Synthetic bone cylinders with 10 mm fracture gap and seven-hole locking reconstruction plates were used. Two groups of bone-plate constructs were assembled: Group 1-three monocortical screws on each fracture side, Group 2-three bicortical screws on each fracture side. In each group nine bone-plate constructs were tested until failure, three each in bending, compression and torsion. In each group, 21 bone-plate constructs were tested for failure in fatigue testing, seven each for bending, compression and torsion. In all static testing no significant differences were found between G1 and G2, except ultimate moment in torsion test (G2>G1; P=0.008). Statistical analysis revealed significant differences between groups in axial compression fatigue testing (G1>G2; P<0.05) and four-point bending fatigue testing (G1<G2; P<0.05) in maximum load, minimum load, maximum moment, and minimum moment. In conclusion, screw length can affect the mechanical properties of locking reconstruction plate. Compared to bicortical screws, monocortical screws were less resistant to bending than axial compression. This must be considered when choosing implant, particularly in fractures under high axial loads.
Keywords: Bone-plate; Fracture; Mechanical study